Public Health Education: Improving Public Understanding and Awareness in Maintaining Health - Atmojo, Muhammad Eko; Kusumo, Mahendro Prasetyo; Perdana, Vicky Alfitra (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Health is very important to humans because good health enables a better, more sustainable life. It is important to stay healthy to ensure life runs smoothly. Various health problems in the community are considered threats that can disrupt activities and the sustainability of life in the future. Through this problem, the community development team assists the Aisyiah Pajangan Sub-District Branch to increase community understanding of maintaining health and preventing disease. This empowerment is carried out through the Participatory Rural Appraisal (PRA) method, which prioritizes the formulation of results based on program implementation needs. In this activity, two main activities serve as solutions to problems: socialization of awareness about the spread and prevention of disease, and mass health checks. This activity aims to build a community in Pajangan Sub-District that is better prepared to prevent disease and to increase public understanding of ongoing health maintenance.